Judicial Politics and Policy-Making in Western Europe - Butler, Andrew S (Victoria University of Wellington Law Review, 1994)
This article is a book review of Mary L Volcansek (ed) Judicial Politics and Policy-Making in Western Europe (Frank Cass, London, 1992). The book is a collection of ten essays which discuss the point where politics and law intersect in six states of Western Europe (France, the United Kingdom, Germany, Belgium, the Netherlands, and Italy), and in two supranational European bodies (the European Communities, and the European Court of Human Rights). In his review, Butler first considers what the collection as a whole has to offer in terms of conclusions. The main conclusion is that it can no longer be credibly maintained that judges are the mere mouthpieces of the law devoid of a policy-making role. The second part of the review focuses on the individual essays found in the book. Butler concludes that the book is a welcome addition to the growing interest in the issues pertaining to judicial involvement in policy-making.